2015
DOI: 10.1021/es504483q
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Synoptic Salinity Mapping To Identify Groundwater–Surface Water Discharges in Lowland Rivers

Abstract: Quantifying distributed lateral groundwater contributions to surface water (GW-SW discharges) is a key aspect of tracking nonpoint-source pollution (NPSP) within a watershed. In this study, we characterized distributed GW-SW discharges and associated salt loading using elevated GW specific conductance (SC) as a tracer along a 38 km reach of the Lower Merced River in Central California. High resolution longitudinal surveys for multiple flows (1.3-150 m(3) s(-1)) revealed river SC gradients that mainly decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 48 publications
3
26
0
Order By: Relevance
“…We conducted the synoptic river surveys 17 times from 2010 to 2012 to examine longitudinal gradients using mobile in situ sensors. Pai et al () identified clear SC gradients in 13 of the 17 surveys, the surveys conducted at flows less than 32 m 3 s −1 . Greater flows resulted in overly diluted conditions for our analysis.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…We conducted the synoptic river surveys 17 times from 2010 to 2012 to examine longitudinal gradients using mobile in situ sensors. Pai et al () identified clear SC gradients in 13 of the 17 surveys, the surveys conducted at flows less than 32 m 3 s −1 . Greater flows resulted in overly diluted conditions for our analysis.…”
Section: Methodsmentioning
confidence: 98%
“…Due to the sparse (relative to our synoptic SW observations) and uneven distribution of GW SC data (Figure a), identifying an objective approach for assigning the groundwater concentration distribution along the river (used to estimate fluxes) was challenging. While our previous work involved an interpolated contour map based on inverse distanced weighting of the closest 12 wells (Pai et al, ), the well data screening discussed above resulted in a sparser spatial coverage (see supporting information Figure S4). After testing several averaging approaches, we assigned the GW concentrations in 1 km river segments, excluding wells located more than 5 km from the river, and averaging the concentration of the 3 wells closest to each segment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synoptic river chemistry surveys (e.g., Cook, ; Harrington et al, ; Pai, Villamizar, & Harmon, ; Smerdon et al, ) were completed along three rivers in the AOSR: the Christina River, the Clearwater River, and the Athabasca River.…”
Section: Methodsmentioning
confidence: 99%
“…Synoptic river chemistry surveys (e.g., Cook, 2013;Harrington et al, 2014;Pai, Villamizar, & Harmon, 2015;Smerdon et al, 2012) were completed along three rivers in the AOSR: the Christina River, the Clearwater River, and the Athabasca River. River water samples were collected from the surface, by hand, at n = 166 sites (n = 80 on the Clearwater and n = 86 on the Athabasca) for chemical analysis.…”
Section: Field Methodsmentioning
confidence: 99%